The crystal structure of poly[2-(4-carboxypyridin-3-yl)terephthalpoly[diaqua-(μ4-2-(6-carboxylatopyridin-3-yl)terephthalato-κ5O,N:O′:O″,O‴)]) cadmium(II)] dihydrate, C28H20Cd3N2O16 - Li Wenqiang; Zhang Jingxiao (Zeitschrift für Kristallographie - New Crystal Structures)
C28H20Cd3N2O16, triclinic, P1‾$P\overline{1}$ (no. 2), a = 7.3205(3) Å, b = 9.9488(5) Å, c = 10.0326(5) Å, α = 104.473(4)°, β = 91.566(4)°, γ = 90.191(4)°, V = 707.19(6) Å3, Z = 1, Rgt(F) = 0.0239, wRref(F2) = 0.0576, T = 293 K.